2019
DOI: 10.2147/cmar.s180802
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of adjuvant chemotherapeutic efficacy of docetaxel plus cyclophosphamide and doxorubicin plus cyclophosphamide in female breast cancer

Abstract: PurposeThis retrospective study presents a comparative analysis of the overall survival and toxicities, as side effects, of docetaxel plus cyclophosphamide (TC) and doxorubicin plus cyclophosphamide (AC). The study measured their efficacies during adjuvant chemotherapy, treating Pakistani breast cancer patients by validating the results obtained, with the published analysis of the same treatment given to US patients.Patients and methodsBetween June 2015 and September 2017, for four chemotherapy cycles, 189 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Therefore, to validate the results of this study "overall trend of change in Hb level" and "overall trend of change in WBC count" of SMTA and rat models were compared with each other. "Overall trend of change in Hb level" was compared with the validated and published results (Adeel et al, 2019). It was observed that statistically (applying paired t-test) there was no significant difference between means of "overall trend of change in Hb level" observed form SMTA and rat models because p-value = 0.795>0.05.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Therefore, to validate the results of this study "overall trend of change in Hb level" and "overall trend of change in WBC count" of SMTA and rat models were compared with each other. "Overall trend of change in Hb level" was compared with the validated and published results (Adeel et al, 2019). It was observed that statistically (applying paired t-test) there was no significant difference between means of "overall trend of change in Hb level" observed form SMTA and rat models because p-value = 0.795>0.05.…”
Section: Discussionmentioning
confidence: 92%
“…This study is carried out for two combinations of chemotherapy including TC and AC, as discussed in our earlier work (Adeel et al, 2019). To calculate "overall trend of change in WBC count", Equation 2 was derived on the basis of a reported equation (Equation 1) (Adeel et al, 2019). Equation 1 was used to calculate "overall trend of change in Hb level".…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations